Escherichia coli CspA stimulates translation in the cold of its own mRNA by promoting ribosome progression - Giuliodori, Anna Maria; Belardinelli, Riccardo; Duval, Melodie; Garofalo, Raffaella; Schenckbecher, Emma; Hauryliuk, Vasili; Ennifar, Eric; Marzi, Stefano (Frontiers in Microbiology, 2023)
E. coli CspA is an RNA binding protein that accumulates during cold-shock and stimulates translation of several mRNAs – including its own. Translation in the cold of cspA mRNA involves a cis-acting thermosensor element, which enhances ribosome binding, and the trans-acting action of CspA. Using reconstituted translation systems and probing experiments we show that, at low temperature, CspA specifically promotes the translation of the cspA mRNA folded in the conformation less accessible to the ribosome, which is formed at 37°C but is retained upon cold shock. CspA interacts with its mRNA without inducing large structural rearrangements, but allowing the progression of the ribosomes during the transition from translation initiation to translation elongation. A similar structure-dependent mechanism may be responsible for the CspA-dependent translation stimulation observed with other probed mRNAs, for which the transition to the elongation phase is progressively facilitated during cold acclimation with the accumulation of CspA.